STOCK PRICE : IMPACT OF SALES GROWTH (SG), CASH TURNOVER (CT) AND DIVIDEND PAYOUT RATIO (DPR) - Suherman, Usep; Nurjanah, Fadila (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This research aims to analyze the influence of Sales Growth (SG), Cash Turnover (CT), and Dividend Payout Ratio (DPR) on Stock Price at PT. Hexindo Adiperkasa Tbk during the 2013-2022 period. The study methodology employed is a descriptive approach utilizing quantitative methods. The objective of this study is to elucidate the correlation between the independent variable and the dependent variable. The research focuses on PT. Hexindo Adiperkasa Tbk. The secondary data source is acquired from the company's official website's annual financial report. The data analysis involved descriptive tests, classical assumption tests, and quantitative testing such as linear regression analysis, correlation, coefficient of determination, and significance tests. The research results show that there are complex fluctuations between the observed variables. Partially, Sales Growth (SG), Cash Turnover (CT), and Dividend Payout Ratio (DPR) do not have a significant effect on Stock Price. Likewise, the three of them simultaneously have no significant effect on Stock Price. The implications of this research highlight the incompatibility of data with existing theory and provide insight into the factors that influence company stock prices. It is hoped that the results of this research can provide information as a basis for consideration, support, and contribution to the company.